Effect of processing parameters on the mechanical properties of high-performance polyethylene fibres in the gel spinning process. I. Spin-draw ratio - Choe, C.R.; Lee, K.H.; Kim, K.H. (1989)
A high-molecular-weight polyethylene solution of 5wt% in paraffin oil was spun through a conical die and xerogel fibres formed by extraction of the paraffin in n-hexane. Hot drawing at 120 degreesC was studied. Tensile strength and modulus increased with increasing draw ratio. - Chemical Abstracts, 112(14), 1990, abstract 120493